Decision Support System for Determining Extracurricular Interest Using the Naive Bayes Method - Azhar, Joehari; Hasugian, Abdul Halim (Newinera Publisher, 2024)
The Decision Support System (SPK) is a tool that can help individuals make more effective and efficient decisions. In the context of education, SPK can be used to assist students in determining extracurricular specializations that suit their interests and talents. This research aims to develop an SPK to determine extracurricular specializations for students using the Naive Bayes method. The Naive Bayes method was chosen because of its ability to classify based on probability. The data used in this study include student profiles, academic scores, and student interest in various types of extracurriculars. The results of the study show that the SPK developed can provide recommendations for extracurricular specialization with quite high accuracy. In addition, the system is also easy to use and can help students make more informed decisions.